Passivity-based posture control of a humanoid robot using a power-conserved transformation. (17th December 2021) - Ozawa, Ryuta; Kakei, Yuki; Ishizaki, Junya
Abstract : This paper proposes a passivity-based regulator for the balance of a humanoid robot. This regulator can dynamically stabilize internal motions as well as the configuration of a floating base. Using a unique transformation that conserves the power, we can rigorously prove the stability of an equilibrium point of the closed-loop system. Moreover, the regulator can be implemented easily since the transformation simplifies an optimization problem to determine the realizable control input and a post-process such as the inverse kinematics. Experiments validate the robustness of the proposed controller to disturbances, including a large angular momentum and large disturbances in the environments. GRAPHICAL ABSTRACT: UF0001